Strengthening of reinforced concrete beams with carbon fibre reinforced plastics - Cheong, Hee Kiat. (2008)
Several techniques to strengthen reinforced concrete structures, such as sprayed concrete, concrete jacketing, or externally bonded plates of steel or composite materials, are available and have been studied in this report.